CORPORATE SOCIAL RESPONSIBILITY: COMPARATIVE ANALYSIS OF THE STATE OF PLAY IN LITHUANIA AND BELARUS - Diskienė, Danuta; Seiliūtė, Jovita (Ekonomika, 2012)
The article reviews the essence and main principles of social responsibility. The content and conception of social responsibility of a business organization is discussed mainly through elaboration of the reasons for business organizations to bear and implement social responsibility. The approach to corporate social responsibility in Lithuania and Belarus is analysed and discussed by comparing the attitudes regarding a wide range of elements related to the corporate social responsibility and its implementation. The approach of business actors of the two countries is collated through different perspectives and angles.